Stochastic assessment of harmonic distortion level of medium voltage radial distribution network - Au M.T.; Milanovi? J.V. (2023)
This paper presents a stochastic assessment of total harmonic voltage distortion (THDv) level of radial medium voltage distribution network using Monte Carlo simulation based on probabilistic harmonic current spectra of typical aggregate load types obtained from harmonic field measurements as inputs. High and low power demand periods of aggregate loads at each network bus are incorporated into the Monte Carlo simulation to account for the influence of power demand on harmonic voltage distortion, which then associate the respective THDv probability distribution curves to specific times of day. Simulation of a case example shows promising and realistic results. Copyright KTH 2006.